Altered Cytokine Endotoxin Responses in Neonatal Encephalopathy Predict MRI Outcomes - O'Dea, Mary Isabel; Kelly, Lynne A.; McKenna, Ellen; Strickland, Tammy; Hurley, Tim P.; Butler, John; Vavasseur, Claudine; EL-Khuffash, Afif F.; Miletin, Jan; Fallah, Lida; White, Arthur; Wyse, Jason; et al. (Frontiers in Pediatrics, 2021)
Abstract: Background: Neonatal Encephalopathy (NE) is associated with adverse neurodevelopmental outcome and is linked with systemic inflammation. Pro-inflammatory and anti-inflammatory cytokines are known to play a role in the pathology of NE by activating innate immune cells. Methods: Eighty-seven infants were enrolled including 53 infants with NE of whom 52 received Therapeutic Hypothermia (TH) and 34 term infant healthy controls (TC). Whole blood sampling was performed in the four days of life and a 14 spot Elisa Multiplex Cytokine Array carried out on baseline samples or after stimulation with Lipopolysaccharide (LPS) as an additional inflammatory stimulus. The cytokines medians were examined for differences between infants with NE and healthy TC, and then short term outcomes of Sarnat Stage, Seziures and MRI brain were examined within the NE group. The potential of LPS stimulation to predict abnormal MRI was explored using (Receiver Operating Characteristic) ROC curves. Results: At baseline, infants with NE had significantly higher levels of erythropoietin (Epo), interleukin (IL)-6 and IL-1ra and significantly lower VEGF than controls. All cytokines were increased after LPS stimulation in infants with NE with an excessive Epo and IL-1ra response compared to controls. Infants with NE had lower IL-8, IL-2, IL-6, tumour necrosis factor (TNF)-α, granulocyte-macrophage colony-stimulating factor (GM-CSF), vascular endothelial growth factor (VEGF) and interferon (IFN)-γ compared to controls following LPS. GM-CSF and IFN-γ, IL-1β, IL-1ra and VEGF were higher on Day 1-2 in NE infants with abnormal neuroimaging. GM-CSF, IFN-γ and TNF-α levels with LPS stimulation were different upon stimulation between normal and abnormal neuroimaging. TNF-α is the only strong cytokine predictor both pre and post LPS stimulation of abnormal brain imaging. Conclusions: Altered cytokine responses are found in infants with NE versus controls and more significant differences are unmasked by the additional stimulus of LPS which potentially improves the predictive power of these cytokines for the detection of abnormal MRI’s. Infants with NE undergoing TH demonstrate both trained immunity and tolerance and understanding these responses will facilitate adjunctive immunomodulatory treatments.